Enhancing employability skills with e-portfolio assessment in tourism internships - Mohd Puad, Mohd Hazwan; Syed Abdullah, Sharifah Intan Sharina; Abdul Karim, Noor Ibtisam (Association of Malaysian Researchers and Social Services, 2024)
The emergence of the digital economy has impacted the employability skills required in the hospitality and tourism industry. The lack of employability skills among tourism students poses a significant challenge in developing their careers in the industry. In today’s digitally focused landscape of the industry, technological advancements need to be adapted in assessing learning activities including internships for tourism students. This paper is an early-stage study on the notion of employability skills, the concept of e-portfolio evaluations in education, and the need to improve employability skills in tourism internship assessment using an e-portfolio. E-portfolio-based assessments reflect on interns’ target strengths and limitations, encouraging self-awareness and self-directed learning as interns have opportunities to record the progress of internship work and experiences. In summary, this paper concludes and recommends that to prepare the future skilled tourism workforce, tourism educators can use the e-portfolio to assess the students’ internship work that will further enhance their employability skills.